Modified tannins for alkyd based anticorrosive coatings - Jovanka N. Kovačina; Mladen D. Bugarčić; Tihomir M. Kovačević; Aleksandar D. Marinković (Zaštita Materijala)
The study of the synthesis of anticorrosive inhibitors, based on chemically modified tannins, and their use in alkyd based coatings to improve anticorrosive properties is presented in this work. Two methods of tannin modification were applied: direct method using ammonium hydroxide, ammonium hydroxide/ammonium chloride buffer or diethylenetriamine (DETA); and a two-step method including tannin modification with epichlorohydrin (ECH) in first step to produce epoxy modified tannin, ET, and further modification with heteroaromatic amines or linseed oil fatty acids (LFA) in second step. The obtained anticorrosive additives were characterized using ATR-FTIR, 1H and 13C NMR spectroscopies and elemental analysis. Epoxy, amino, hydroxyl, acid and iodine values of the synthesized inhibitors were determined according to standard methods. The prepared alkyd coating with tannin inhibitors was tested according to standard SRPS EN ISO 4628 method. Anticorrosive coating containing modified tannin based additive showed increased anticorrosive properties, good adhesion and coverage comparing to the coating with zinc phosphate additive. The alkyd coating films based on ET-LFA and ET modified with 2-amino-5-mercapto-1,3,4-thiadiazole showed best anticorrosive results.